2014
DOI: 10.4238/2014.june.9.16
|View full text |Cite
|
Sign up to set email alerts
|

Case Report Familial balanced translocation leading to an offspring with phenotypic manifestations of 9p syndrome

Abstract: ABSTRACT. We report two similarly affected cousins (children of monozygotic twin sisters) with phenotypic features consistent with 9p deletion syndrome, including dysmorphic craniofacial features (trigonocephaly, midface hypoplasia, upward-slanting palpebral fissures and long philtrum), intellectual disability and disorders of sex development. Initial cytogenetic examination showed normal karyotypes in the probands and their respective parents, though multiplex ligation probe amplification revealed a 1q termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…The authors concluded that the critical region responsible for 9p deletion syndrome lay within a 300 Kb region on 9p22.3. Abreu et al ( 2014 ) reported two cousins who were born to identical twin sisters and had a deletion in the 9p24.3 region associated with the phenotype of 9p deletion syndrome. In that study, although FISH and multiplex ligation‐dependent probe amplification (MLPA) techniques with probes that covered only copy number variants at the telomeric regions, were used, the authors postulated that the deletions were only located at these sites.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the critical region responsible for 9p deletion syndrome lay within a 300 Kb region on 9p22.3. Abreu et al ( 2014 ) reported two cousins who were born to identical twin sisters and had a deletion in the 9p24.3 region associated with the phenotype of 9p deletion syndrome. In that study, although FISH and multiplex ligation‐dependent probe amplification (MLPA) techniques with probes that covered only copy number variants at the telomeric regions, were used, the authors postulated that the deletions were only located at these sites.…”
Section: Discussionmentioning
confidence: 99%
“…13 En las pacientes expuestas, no hubo alteraciones genitales y/o gonadales, lo que podría deberse a que estas son más frecuentes en individuos masculinos. 6,14 No se ha encontrado alguna característica clínica presente en todos los casos de monosomía 9p24. 7,[10][11][12] Las pacientes expuestas compartían la malformación del sistema nervioso central, narinas antevertidas, anomalías en pabellones auriculares y filtrum largo.…”
Section: Discussionunclassified